Buinesses along muddy Front St., Nome, Alaska between 1898 and 1900 - Hester, Wilhelm, 1872-1947 (1898)
Businesses identified: S.S. Tacoma, S,S, Centenial, Warwick Hotel, and Bodega Saloon. Written on verso: Front St. PH Coll 318.1063 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number